Economic growth and social inclusion: The recent peruvian experience and the new constitutional government - Cornejo Ramírez, Enrique (2011)
For more than a decade, Peru has experienced substantial economic growth including constant reduction of poverty and inequality. This essay shows that the unprecedented results of the Peruvian economic history are due to two factors: the application of orthodox economic policies and stability of these politics despite of governmental turnover. The successful economic results, in conjunction with social investment that improved distribution of growth income, have translated themselves into diminishing rates of poverty and inequality. This scenario is maintained in the economic model which has been adopted by President Ollanta Humala.